2005
DOI: 10.1074/jbc.m413255200
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Role of H-NS and GadX in the Regulation of the Glutamate Decarboxylase-dependent Acid Resistance System in Escherichia coli

Abstract: One of the most efficient systems of acid resistance in Escherichia coli, the gad system, is based on the coordinated action of two isoforms of glutamate decarboxylase (GadA and GadB) and of a specific glutamate/␥-aminobutyrate antiporter (GadC). The gadA/BC genes, activated in response to acid stress and in stationary phase cells, are subjected to complex circuits of regulation involving 70 , S , cAMP receptor protein, H-NS, EvgAS, TorRS, GadE, GadX, GadW, and YdeO. Herein, we provide evidence that the nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 43 publications
(72 reference statements)
3
63
0
Order By: Relevance
“…2A and B, the only gene that affected these systems was gadE. The gadA, -X, and W genes, with proven roles in acid resistance, were tested in earlier studies (16,33,44,50,52). Failure to see an effect of the other AFI genes (yhiF, yhiD, hdeB, hdeA, hdeD, or yhiUV) conflicted with some of the earlier studies noted above but suggested that the methodology of testing is important in revealing the roles of these gene products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2A and B, the only gene that affected these systems was gadE. The gadA, -X, and W genes, with proven roles in acid resistance, were tested in earlier studies (16,33,44,50,52). Failure to see an effect of the other AFI genes (yhiF, yhiD, hdeB, hdeA, hdeD, or yhiUV) conflicted with some of the earlier studies noted above but suggested that the methodology of testing is important in revealing the roles of these gene products.…”
Section: Resultsmentioning
confidence: 99%
“…Most notable are gadA, encoding an isozyme of glutamate decarboxylase (45,47), and gadE, the essential activator of glutamate-dependent acid resistance (22,30). Two other genes in this region, GadX and GadW, are involved in modulating gadE expression as well as the expression of gadA and gadBC (16,32,33,44,(48)(49)(50)52). However, the contribution of other AFI genes toward acid resistance has remained unclear.…”
mentioning
confidence: 99%
“…Regulation of the hdeAB operon. The figure has been produced using data from the literature (8,13,16,20,22,24,26,27,30,33,37,39,42,43,44,46) as well as the results obtained in this study. Thick arrows represent genes.…”
Section: Resultsmentioning
confidence: 99%
“…The gadA (monocistronic) and gadB (processed) mRNAs are similar lengths (approximately 1.5 kb) and therefore have similar electrophoretic mobilities on an agarose gel. The H-NS binding sites responsible for gadA repression (14) are indicated. The GadX/GadW binding sites described in this paper are indicated by solid ellipses.…”
mentioning
confidence: 99%